Intra-family sexual violence: disclosure, harm reduction and prevention (Research, Society and Development, 2021)
This article is part of a larger project, carried out with the participation of teenagers and young adults studying at the Federal University. It is a descriptive research with qualitative orientation, in which we used the data collection technique of Oral History, the oral accounts of life, of the participants who confirmed having suffered some type of intrafamilial sexual violence during childhood and/or adolescence. We aimed to learn about the stories and characteristics of intrafamilial sexual violence, in order to think about disclosure, prevention and harm reduction. Reports indicate that survivors of intrafamilial sexual violence fear family reaction to the disclosure, fear being discredited and/or blamed for the sexual violence, feel guilty even though knowing they were vulnerable subjects in violent situations. In this study, part of our participants did not disclose the sexual violence immediately because they did not know or were unsure of the meaning of sexual violence at the time. Others feared for their family members and the sadness, anger and emotional lack of control that the truth could cause them, worrying about the possibility of experiencing more violence. We consider it essential that children and teenagers be warned about the possibility of sexual violence, as well as that they be educated about the forms of manifestation, knowing the possibility of the abuser being someone they trust, a family member or a family friend, orienting that all violence must be disclosed to an adult as many times as necessary, because often the revelation is not accepted, nor the violence is interrupted.